0091 REM Sleep Has No Effect on Consolidation of Emotionally Salient Information Seen in Animated Threat Detection Task. (27th April 2018) - Mertens, N A; Bryant, N B; Gill, H A; Jones, A P; Robert, B; Clark, V; Pilly, P K
Abstract: Introduction: Previous literature has shown the amount of rapid eye movement (REM) sleep is associated with the encoding and consolidation of emotionally salient information, typically represented through real life IAPS images. However, it is currently unknown if REM sleep will affect encoding of emotionally salient stimuli from an animated threat detection task. The current study hypothesizes that as participants view more animated emotionally salient information, the amount of REM sleep they experience will be related to better overall task performance the following morning. Methods: Twenty-five healthy participants completed a computerized task wherein they determined whether a stationary scene contained a threat. During the training phase, individuals viewed short animated clips providing feedback on their choice. Misses (failing to correctly identify a threat) featured emotionally salient images (e.g. bombs exploding or individuals being shot). After completion of the task participants slept while polysomnography was recorded. Change in performance between testing without feedback immediately following training was compared to the following morning upon awakening. Results: Results suggest there was no significant effect of total REM sleep on the general performance of the threat detection task the following morning (p=.470). The number of misses and by extension the amount of negative feedback the participants received during training also had no influence on post-sleep general performance (p=.455). Conclusion: While previous studies have shown there is a relationship between REM sleep and the consolidation of emotional salient images, the present study found no such effect using visual search tasks containing emotionally salient imagery during feedback in training. Further research should focus on how quality of animation and previous experience with animated media affects the relationship between REM sleep and consolidation of emotional stimuli. Support (If Any): This material is based upon work supported by the DARPA and the Army Research Office under Contract No. W911NF-16-C-0018. Any opinions, findings, and conclusions or recommendations expressed in this material are those of the author(s) and do not necessarily reflect the views of the DARPA or the Army Research Office.